Optimization of Protein Content in Earthworm-based Fish Feed Formulation for Catfish (Clarius gariepinus) - Zarina, Zakaria; N oor Hasyierah, Mohd Salleh; Alina Rahayu, Mohamed; Ahmad Anas, N.G.; Siti Nur Amirah, Idris (Universiti Kebangsaan Malaysia, 2013)
Link to publisher’s homepage at http://www.ukm.my/jsm/utama.html